The Role of Ethnosolfeggio in the Preservation and Development of Kazakhs' Song Heritage in the Conditions of Globalization - Aigul K. Baibek (Publishing house "Sreda", 2019)
The article is devoted to the problem of preserving the spirit and creative potential of the traditional music in the modern Europeanized education of folk musicians in Kazakhstan. In the modern ethnosolfeggio course, adapted for folk singers, the necessary basis is formed for understanding the historical development of traditional music and its role in modern cultural contexts, as well as the need for its preservation and further development. The purpose of the article is to offer the measures to preserve the valuable qualities of traditional music and ensure its further development. Based on the methods of generalizing pedagogical experience (observation, studying normative documentation, questionnaires), many years of experience in teaching a course of ethnosolfeggio adapted for folk singers are presented. As a result of the work, the necessary theoretical and practical basis was obtained for understanding the historical development of traditional music, understanding its role in modern cultural contexts and the need for its preservation and further development. The article concludes that ethnosolfeggio course include saturation with creative forms of work that rely on «verbalness» inherent to traditional singers, and emphasis on mastering improvisation that unfolds the composing potential.